2020
DOI: 10.3390/nano10040764
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of 2D Materials

Abstract: Since the great success of graphene, atomically thin layered nanomaterials—called two-dimensional (2D) materials—have attracted tremendous attention due to their extraordinary physical properties [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…It has been reported that the synaptic plasticity is a basic characteristic of memristors for neuromorphic computing. [35][36][37][38] In this work, since the OVs-LN-OVs memristor has the memristive behavior at negative bias, negative set voltage pulses (V set = −21 V) were applied to TE, and the conductance was recorded by the reading voltage (V read = −2 V), as presented in Fig. S5(a).…”
Section: Plasticity and Multi-rsmentioning
confidence: 99%
“…It has been reported that the synaptic plasticity is a basic characteristic of memristors for neuromorphic computing. [35][36][37][38] In this work, since the OVs-LN-OVs memristor has the memristive behavior at negative bias, negative set voltage pulses (V set = −21 V) were applied to TE, and the conductance was recorded by the reading voltage (V read = −2 V), as presented in Fig. S5(a).…”
Section: Plasticity and Multi-rsmentioning
confidence: 99%
“…At the forefront of materials research are 2D materials. 2D materials are materials with a thickness of one or a few atoms that have remarkable qualities because of their distinct structural features at the nanoscale . High-quality 2D materials have been made possible by a contamination-free, one-step, universal Au-assisted mechanical exfoliation process that dates back to the initial separation of graphene .…”
Section: Introductionmentioning
confidence: 99%
“…2D materials are materials with a thickness of one or a few atoms that have remarkable qualities because of their distinct structural features at the nanoscale. 6 High-quality 2D materials have been made possible by a contamination-free, one-step, universal Au-assisted mechanical exfoliation process that dates back to the initial separation of graphene. 7 This method uses sticky tape to gently remove layers from a bulk substance in preparation for small-sized, randomly shaped materials.…”
Section: Introductionmentioning
confidence: 99%